2009
DOI: 10.1007/s00467-009-1266-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth in boys with idiopathic nephrotic syndrome on long-term cyclosporin and steroid treatment

Abstract: Although steroid-free remission can usually be achieved with cyclosporin A (CsA) in patients with steroid-dependent nephrotic syndrome (SDNS), some CsA-treated patients require long-term steroid therapy. Data on growth in these patients are scarce. Sixty-four boys with SDNS receiving long-term CsA and steroid therapy were retrospectively analyzed. During the 10-year follow-up period, height standard deviation score (HSDS) remained in the normal range in 47 patients but was below -2 SD in 17 patients. The occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…The observed effects of GC on growth were in accordance with those reported previously 11,12) . The cumulative dose of GC and height at the time of diagnosis were correlated with the linear growth of patients.…”
Section: )supporting
confidence: 92%
See 1 more Smart Citation
“…The observed effects of GC on growth were in accordance with those reported previously 11,12) . The cumulative dose of GC and height at the time of diagnosis were correlated with the linear growth of patients.…”
Section: )supporting
confidence: 92%
“…Results of other studies of the effects of immunosuppressants on the growth of nephrotic patients have suggested that growth retardation is caused mainly by long-term use of GC, and not by other immunosuppressants 1,10,11) . However, heterogeneous types and doses of immunosuppressants including CsA and mycophenolate mofetil were used in these studies.…”
Section: )mentioning
confidence: 99%
“…This study found that median height was stable throughout the first 5 years but that reductions in height SDS progressed over time, becoming statistically significant at 9 years. 38 Although most patients in this study did not reach the height of their genetic potential, adult height was normal for all but 2 patients. Interestingly, no correlation between cumulative steroid dose and change in height was found.…”
Section: Growthmentioning
confidence: 59%
“…In contrary, Leroy et al (2009) (19) followed 64 children with SDNS receiving long-term cyclosporine and steroid therapy which were retrospectively analyzed. During the 10-year follow-up period, height standard deviation score (HSDS) remained in the normal range in 47 patients but was below -2 SD in 17 patients.…”
Section: Moon Et Al (2014)mentioning
confidence: 99%